Lysine Analogue Use and Thromboembolic Risks: An Evidence Based Analysis - Montroy, Joshua (Université d'Ottawa / University of Ottawa, 2018)
Allogenic blood transfusions, although potentially life-saving, are associated with increased risk of infection, fluid overload, thrombosis, and death. Minimizing exposure to blood products is important for patients and the healthcare system. Antifibrinolytic lysine analogues are effective antihaemorrhagic agents used for the reduction of blood loss and subsequent need for transfusion. However, the pharmacologic mechanism of decreased clot breakdown would suggest the medications should increase the risk of venous thromboembolic adverse events. Trials of lysine analogue administration are often underpowered to detect the effect of these medications on thrombotic events. As lysine analogue use increases for blood loss reduction, there is an important need for research dedicated to the safety of lysine analogues, especially in patients who are at highest risk of venous thromboembolism. Through systematic review and meta-analyses, we investigated the use of lysine analogues in cancer patients, where VTE is particularly prevalent. We identified that only a small number of trials have been performed in cancer patients. Among available data, similar reduction of transfusion was observed in cancer patients treated with lysine analogues compared to non-cancer patients. However, we also found that existing data was grossly underpowered to determine the effect of lysine analogues on risk of VTE (Peto odds ratio (OR) 0.60; 95% CI 0.28-1.30). By administering lysine analogues topically, as opposed to intravenously, systemic absorption of the drug may be limited, and the occurrence of unwanted side-effects may be minimized. We also reviewed the published literature to determine if there was sufficient evidence to support topical application of tranexamic acid. Topically applied tranexamic acid effectively reduces both transfusion risk and blood loss and no increased risk of VTE events was observed (pooled OR=0.78, 95% CI 0.47 to 1.29). However, none of these studies included cancer patients and the vast majority of the trials were in orthopedic surgery. Lastly, we sought to determine the extent to which lysine analogues are currently used at a large tertiary care academic institution. In addition, we explored which factors influenced lysine analogue use, and areas of informational or study need. Surgeons reported low lysine analogue use, and the timing of administration varied considerably. Many surgeons (66%) believed a clinical trial was needed to demonstrate the efficacy of lysine analogues in their respective surgical field, and 59% felt a trial was needed to demonstrate that the medication was safe in their patient population. We confirmed that there are only a few studies evaluating the effect of lysine analogues in cancer patients and that many surgeons are concerned about the safety profile of these medications. Surgeons may feel more comfortable administering these agents topically as opposed to intravenously, and while this may be a safer option, there has been limited evaluation of this approach outside of orthopedic procedures.
Keywords: Cancer; Venous thromboembolism; Lysine analogue; Blood transfusion; Surgery